Architectural choices for cyber resilience. Issue 1 (1st January 2019) - Brennan, Geoffrey; Joiner, Keith; Sitnikova, Elena
ABSTRACT: Open system architectures have been proposed as a solution to addressing issues surrounding the acquisition of mission-critical platforms and critical infrastructure. These issues relate to the extended timeframes associated with introducing advanced and complex systems at a rate commensurate with technological and threat advancement. Adopting an open system architecture helps to address these issues but comes with considerations that influence the capacity for those systems to maintain cyber resilience. Generally, these considerations relate to the use of openly available interface standards, the capability for dynamic network management, maturity of processes and, the ability for platforms to evolve in response to emerging cyber threats. This paper discusses advantages and disadvantages of a bespoke or open architecture and highlights the impact of each approach on mission-critical platforms. The resulting recommendations focus on using a project's projected lifecycle to indicate the most suited architecture and therefore leverage the relative benefits of each methodology.